PERANAN TUMBUHAN OBAT DALAM BUDAYA ANAK SUKU MOILE DI MOKWAM MANOKWARI - Simon Sutarno (FMIPA Universitas Papua, 2010)
The objective of the research was to determine the role of medicinal plants in the livelyhood of children in the sub-tribe Moile. The study was conducted in the area of Mokwam in July 2008. Analysis of Index of Cultural Significance (ICS) is used to measure the role of medicinal plants in the culture of the sub-tribe Moile. The results showed 10 species of plants that have a major role in the lives of children from the sub-tribe Moile. The ten species of plants are Hornstedtia scottiana, Myrmecodia sp1, Myrmecodia sp2, Begonia sp8, Begonia sp9, Actinidia latifolia, Alpinia oseanica, Laportea theterupta, Imperata cylindrica, and Musa sp2.